Penerapan Model Pembelajaran Collaborative Learning terhadap Hasil Belajar PKn pada Siswa - Juliyani, Juliyani; Prananosa, Ahmad Gawdy; Firduansyah, Dedy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the completeness of the learning outcomes of Civics students of grade IV of Durian Terung Elementary School after the implementing the Collaborative Learning model. The method used in this research was a quasi experimental method and the research subjects were all fourth grade students at Durian Terung State Elementary School. The research result showed that the average pre-test score was 47,90. After treatment using the collaborative learning model was implemented in class IV, the average post test score increased to 79,95. The result of this research conclude that there is a difference in the average scores of students before and after using the collaborative learning model. Keyboard: Collaborative Learning, Learning outcomes, PKN